Rituals Pattorani In the Masalima Island Community, Pangkep Regency (Cultural Studies Islam) - Amirullah, Amirullah (Yayasan Adra Karima Hubbi, 2024)
Background. Pattoraniis a ritual carried out before the arrival of Islamic teachings which is based on mythical community beliefs. Rituals pattoranicarried out once a year on Masalima Island, Pangkep Regency. Purpose. This research aims to explain the origins of the ritualpattorani.Through a form of Islamic cultural analysis. So you will find forms of Islamic culture in ritualspattoraniwhich was carried out by the people of Masalima Island, Pangkep Regency. Method. The method used, qualitative observation is a method carried out in direct recording in the field. Results. The first series of pattorani rituals at the puggawa's house continued on the beach then on the boat with several rituals, namely:Pakkaja's parents, appassili biseang, andacaru-caru beseangafter that the fishermen's wives had a meal together near the bridge, and pamacca activities were also held, after the seasonpattoranithen a second meal was held while listening to religious lectures and prayers. ritualpattoraniThere are forms of acculturation of local culture with Islamic culture, namely: prayer, reading barazanji, religious lectures, and sholawatan and in which there are Islamic values such as spiritual values and the value of cooperation. Conclusion. RitualspattoraniThere are forms of Islamic culture, namely: Prayer, the reading of barazanji which is read during rituals on a boat during umandemande (together eating) activities. Not only reading the book of barazanji, but we can also see and watch religious lectures and sholawatan during the second group meal held after the season.pattorani, a religious lecture delivered by a cleric who gave advice on gratitude for sustenance.